Lithium, magnesium and uranium isotope behaviour in the estuarine environment of basaltic islands - Pogge von Strandmann, P; James, R; van Calsteren, P; Gislason, SR; Burton, K (2008)
This study presents major and trace elements and uranium (U), lithium (Li) and magnesium (Mg) isotope data for dissolved and suspended particulate material from estuaries draining dominantly basaltic terrains in Iceland (Borgarfjörethur) and Sao Miguel (Povoação) in the Azores archipelago. The concentrations of dissolved sodium (Na), calcium (Ca), potassium (K), sulphate (SO 4), Mg and Li, and 7Li/ 6Li and 26Mg/ 24Mg isotope ratios vary directly as a function of the dissolved chloride concentration [Cl], indicating that these species are non-reactive in these estuaries. However, U appears to be affected either by colloid flocculation or the formation of Fe-oxyhydroxides in Borgarfjörethur. The major element composition of suspended particulate material in the estuary at Borgarfjörethur shows that the detrital silicates delivered to the estuarine mixing zone are relatively unweathered. Accordingly, the δ 26Mg isotope composition of the suspended material is indistinguishable from that of the parent basalts. However, the ( 234U/ 238U) activity ratios of the suspended material are significantly different from the parent basalt indicating rapid equilibration of the U isotopes between particles and seawater. The Li concentration and δ 7Li isotope composition of the suspended load are also observed to increase with increasing [Cl], consistent with ongoing weathering of detrital material and the formation of secondary minerals in seawater. Depending on the particle residence time in the estuary, this process could remove as much as 15-25% of the global riverine input of Li to the ocean. © 2008 Elsevier B.V. All rights reserved.